Comparison of rubber band ligation with 3% polidocanol injection sclerotherapy for the treatment of internal haemorrhoids at a Nigerian tertiary hospital - Makanjuola, Ayomide; Balogun, Olanrewaju; Osinowo, Adedapo; Adesanya, Adedoyin; da Rocha, John (The Nigerian postgraduate medical journal, 2020)
Background: The surgical treatment of internal haemorrhoids is yet to be fully elucidated. Rubber band ligation (RBL) and injection sclerotherapy (IS) are less invasive alternative day-case treatment options with lower morbidity than excisional haemorrhoidectomy. Aims: This was a prospective study that compared the efficacy of RBL with 3% polidocanol IS in the treatment of Grades I to III internal haemorrhoids. Patients and Methods: Sodergren haemorrhoid symptom severity (SHSS) scores of consecutive adult patients with internal haemorrhoids were calculated before and after each of three therapy sessions with RBL and IS. Outcome measures included SHSS scores after treatment, post-procedure pain and complication rates. Data were collated and analysed using SPSS version 23. Results: A total of 74 patients participated in the study with 37 patients in each treatment group. The RBL and IS groups were not statistically different in age (P = 0.506), weight (P = 0.117), height (P = 0.462), BMI (P = 0.153) and gender (P = 0.639). The mean SHSS scores for both groups before therapy (P = 0.876), at 4 weeks (P = 0.669), 8 weeks (P = 0.168) and 12 weeks (P = 0.391) after commencement of therapy were not statistically different. The SHSS scores at 12 weeks after treatment were statistically significantly lower than before treatment in both the groups (P < 0.01). The post-procedure pain score was significantly higher in the RBL than IS group after the first (P < 0.001) and second (P < 0.006) but not after the third therapy session (P = 0.501). The complication rates were low and not significantly different for the RBL and IS groups (5.7% versus 8.1%; P = 0.643). Conclusion: The study concluded that RBL and IS are both effective and safe in the treatment of Grades I, II and III internal haemorrhoids.